Perception of Employees on Environmental Management System in the United Arab Emirates: Evaluating and Overcoming the Challenges to its Implementation among the Manufacturing Industries - Veera Kumar, Mohan (UNIMAS, 2023)
With the speed of industrialization, a large number of industries have come up to meet the demands of the growing population and with this, the consumption of fossil fuels has increased. This harms the environment due to the emission of greenhouse gas, air pollution, climatic changes, and contamination of drinking water. With this thought, many organizations are adopting Environmental Management System (EMS) as a part of the ISO management system with substantial numbers of certifications to address quality management in the manufacturing industries. The United Arab Emirates (UAE) has the highest per capita electricity consumption, with 12.5 MWh in 2020, and emits 50% of the total CO2 produced in the country. The issue of global warming has also increased, contributing to water scarcity, drought, aridity, and a hot climate for most of the year. Considering this situation, the study aimed at evaluating the implementation of EMS, and analyse key drivers, challenges, and the improvements required to overcome the challenges faced by the manufacturing industries in the UAE based on the opinions of the employees. The main methodology adopted was the questionnaire-based survey that helped to gather enormous data on the EMS adopted and implemented in the manufacturing industries in UAE. The questionnaire contained 80 different closed-ended questions based on 4-point Likert scale divided into six parts that comprised the demographic profile of the employees, the effectiveness of EMS implementation in the manufacturing sector, benefits of EMS implementation, drivers of EMS implementation, challenges faced by the organization in the EMS implementation and improvements required in the EMS implementation. After the questionnaires were formed, a preliminary test was conducted for the validation and reliability of the questionnaire using Cronbach’s Alpha. Simple random sampling was done and the questionnaire was distributed to 475 employees of different levels such as technicians/workers, supervisors, middle management and senior management of the different manufacturing industries in Abu Dhabi, UAE. The reliability test was performed to evaluate the functionality of EMS in the manufacturing sectors. Hypothesis on the association between the implementation of EMS and the functions was conducted by using the Chi-square test. The findings based on the perception of employees revealed that a lot of challenges are faced at the time of implementing EMS due to the lack of awareness, limited technical support resources, lack of expertise, and less knowledge which hinders manufacturing firms in Abu Dhabi to invest in EMS. The results also found that EMS is beneficial for organisations as it improves the conservation of resources, the company's image, and waste minimization. The study highlighted that EMS practices in manufacturing industries can reduce environmental issues like reduction of pollution, augmentation of recycling propensities, and enhancement of sustainable resource utilization. The results inferred that effective implementation of EMS is dependent on the commitment of the top management in the organization, training of the employees, and proper enforcement of the regulations.